2012
DOI: 10.1007/s00224-012-9411-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lower Bounds on the Price of Stability of Undirected Network Design Games

Abstract: Abstract. Bounding the price of stability of undirected network design games with fair cost allocation is a challenging open problem in the Algorithmic Game Theory research agenda. Even though the generalization of such games in directed networks is well understood in terms of the price of stability (it is exactly H n , the n-th harmonic number, for games with n players), far less is known for network design games in undirected networks. The upper bound carries over to this case as well while the best known lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…In similar context, other papers considered (group)strategy proof and efficient mechanisms Regarding network design games, there is a long line of works mainly focusing on fair cost allocation (Shapley cost-sharing mechanism), originated by [5]. Anshelevich et al [5] showed a tight (log k) bound on the PoS for directed networks, while for undirected networks several variants have been studied [11,12,22,24,35] but the exact value of PoS still remains an open problem. For multicast games, Li [56] proved an upper bound of O(log k/ log log k), while for broadcast games, Fiat et al [39] proved an O(log log k) upper bound which was improved to constant due to Bilò, Flammini and Moscardelli [13].…”
Section: Related Workmentioning
confidence: 99%
“…In similar context, other papers considered (group)strategy proof and efficient mechanisms Regarding network design games, there is a long line of works mainly focusing on fair cost allocation (Shapley cost-sharing mechanism), originated by [5]. Anshelevich et al [5] showed a tight (log k) bound on the PoS for directed networks, while for undirected networks several variants have been studied [11,12,22,24,35] but the exact value of PoS still remains an open problem. For multicast games, Li [56] proved an upper bound of O(log k/ log log k), while for broadcast games, Fiat et al [39] proved an O(log log k) upper bound which was improved to constant due to Bilò, Flammini and Moscardelli [13].…”
Section: Related Workmentioning
confidence: 99%
“…In the special case of broadcast games, in which there is a single source and each other node is the sink node of a different agent, the PoS was shown to be a constant [7]. Lower bounds on the PoS in the undirected case were studied in [6], where it was shown that the PoS can be as high as 348/155, 1.862, and 20/11 in general games, single-source games, and broadcast games, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…[5] showed a tight Θ(log k) bound for directed networks, while for undirected networks several variants have been studied [14,16,21,23,28,29,45,15] but the exact value of PoS still remains a big open problem. For multicast games, an improved upper bound of O(log k/ log log k) is known due to Li [45], while for broadcast games, a series of work [29,44] lead finally to a constant due to Bilò et al [16].…”
Section: Example 12 (Generalized Weighted Shapley)mentioning
confidence: 99%